Adhesion of flexor hallucis longus at the site of a tibial-shaft fracture – A cause of a checkrein deformity. Issue 1 (March 2015) - Yuen, C.P.; Lui, T.H.
Highlights Hallux flexus deformity can follow a tibial fracture. It can be due to FHL muscle contracture following deep posterior compartment; entrapment of FHL tendon or fibrous adhesion. Associated flexion deformity of the second and third toes can occur due to the interconnection of the FHL and FDL tendons at the master knot of Henry.